Peluang dan Tantangan Gerakan Penyelamatan Rawa Tripa Berbasis Komunitas di Provinsi Aceh - Monalisa Monalisa (Jurnal Agrisep, 2014)
Abstract. Rawa Tripa is a peat forest area in Nagan Raya Subdistrict, Aceh Province with diverse ecological benefits as well as high content of carbon that plays an important role in minimizing the effect of greenhouse gas on earth. Yet, the preservation of ecosystem in the region is currently threatened due to the reduction of peat land cover area and other environmental damages. One of the causes of the reduction of the total area of the region is the plantation production activity done by several oil-palm plantation companies operating in the area of Rawa Tripa. In relation to the current environmental damages, a number of parties and stakeholders in Aceh Province have taken an initiative to take a joint action to save Rawa Tripa and one of the actions taken is done through a community-based approach. The community-based environmental movement has been regarded as an alternative solution to solve a number of environmental problems. Community approach which is also known as partnership-based approach or community participation in maintaining the natural resource preservation and management. Various constraints founded in supporting the effectiveness of this community-based environmental protection movement are, among other things, the lack of joint commitment to maintain the preservation of this area, and the parties with different interests and paradigm in managing the natural resources in Rawa Tripa. The factors which can support the successful of the environmental movement are the harmonious ideas and agendas of the parties implementing the movement or action and the high level of local community participation.